Paciente masculino de 31 años de edad, diabético e hipertenso y presenta sobrepeso. - Sánchez Jaime, Diego Fabricio (2019)
The present clinical case reveals a 31-year-old male patient with a height of 1.65 meters and weighing 69 kg, was diagnosed diabetic and hypertensive 2 years ago, is currently overweight and comes to the clinic for presenting symptoms: excessive thirst, fatigue, blurred vision, tingling in the hands and feet, accompanied by headache and vertigo, in the biochemical examinations it presents high blood glucose, cholesterol and altered triglycerides, the general practitioner decides to refer him to the nutritionist; when performing the anthropometric assessment, it presents a BMI of 25 kg / m2, waist circumference of 112 cm. and in the 24-hour reminder a hyperhydrocarbon diet, without physical activity. The objective of the nutritional intervention is to improve the nutritional status of the patient and the referred symptoms, reduce the clinical manifestations of diabetes and hypertension that may affect the future. Patient needs nutritional treatment where they will proceed to the elaboration of a food plan, to improve their nutritional status and reduce the symptoms presented.